Penguatan Pengelolaan Keuangan Pada UMKM Desa Rancabango Tarogong Kaler Garut - Marlina, Siska; Rosmayati, Irma; Harahap, Eliya Fatma (Ikatan Cendekiawan Muda Akuntansi, 2024)
Accounting-based financial management can provide benefits for SMEs to know the exact financial condition of the business, regulate and control all financial transactions that occur throughout the sustainability of their business. Strengthening SMEs must of course also be accompanied by financial reports which are an important aspect for the progress of the company through accounting. However, SMEs in villages or remote areas have not been touched by official government institutions in developing their businesses, so the role of universities in community service can be a solution in developing and strengthening the existence of these SMEs. SMEs often feel confined in their ability to apply accounting because they are not used to practicing accounting in managing their business finances. The purpose of community service activities is to provide strengthening of financial management for SMEs in Rancabango Tarogong Kaler Garut Village and to provide training in making financial reports for SMEs in Rancabango Tarogong Kaler Garut Village. So that the output produced from community service activities is to increase the understanding of SMEs about working capital management practices, capital structure management and the use of capital budgeting techniques and be able to practice and apply financial records into financial reports. Community service activities are carried out through mentoring, socialization and strengthening of financial management in MSMEs in Rancabango Village, Tarogong Kaler, Garut.